Zero stars do not recommend : a novel - Wassmer, M J (Sourcebooks Landmark, 2024)
"Professional underachiever Dan Foster is finally taking a vacation. Sure, his life has been average at best and, yeah, he has never quite lived up to his potential. But after a few Miller Lites in paradise with his girlfriend Mara, things are starting to look up. Then the sun explodes. With the island suddenly plunged in darkness (and Mara pestering him for not springing for the up-charged travel insurance), Dan's holiday takes a surprising turn when the elite guests install themselves as the new ruling class. As temperatures drop and tensions rise, revolution begins to brew on the island, and Dan accidentally becomes a beacon of hope for the surviving vacationers. But when one six-person plane is discovered that could send them back to the mainland, Dan realizes he has a choice to make. Does he find a way to escape the island with Mara? Or does he stay and fight to become the most unlikely hero of the end of the world?"--